The Role of Surgical Intervention in the Treatment of Gallbladder Diseases (Cholelithiasis) - Abdusalomovich, Boltayev Nodirjon; Fozil qizi, Mamatova El’mira; Nayim qizi, Ne`matova Roziya (American Journal of Bioscience and Clinical Integrity, 2025)
Gallbladder diseases, particularly cholelithiasis, represent a significant health concern worldwide, often leading to acute complications that necessitate surgical intervention. This study reevaluates the role of surgical methods in the modern management of cholelithiasis, incorporating recent advances in minimally invasive surgery and patient-centered outcomes. Drawing on a cohort of 180 patients from two tertiary hospitals between 2021 and 2024, the research compares the clinical efficacy, cost-effectiveness, and long-term outcomes of laparoscopic and robotic-assisted cholecystectomy, alongside traditional open surgery. Findings reveal that robotic-assisted surgery shows superior precision and lower complication rates in complex cases, though laparoscopic cholecystectomy remains the most cost-effective and broadly applicable option. The study underscores the evolving standards in gallbladder surgery and emphasizes the need for context-specific treatment algorithms, surgeon training, and integrated postoperative care strategies.